The Synthesis, characterization and anti-cancer activity of gold (III) and nickel (II) metal ion complexes derived from tetrazole – triazole compound: gold (III) and nickel (II) metal ion complexes derived from tetrazole – triazole compound - Alrubaye, Afnan (Al-Nahrain Journal of Science, 2022)
This research is for academic understanding to work out new ligand behavior 4-({(5-(4-hydroxyphenyl)-3-sulfanyl-1H-1,2,4-triazol-1-yl)amino}(1H -tetrazol-5-yl)methyl)-2-methoxyphenol (L) with gold (III) and nickel (II) metal ions. Ligand (L) has been synthesized from cyclization reaction of (4-hydroxy-3-methoxyphenyl){[5-(4-hydroxyphenyl)-3-sulfanyl-1H-1,2,4-triazol-1-yl]amino}acetonitrile (F) with sodium azide. α-amino nitrile compound (F) intern synthesized from interaction of aldehyde amine and KCN acidic medium as three components one pot reaction. The presence of well oriented donor atoms (N2 - type) of ligand (L) interacted with gold (III) and nickel (II) ions under reflux to prepare [1:2] [M:L]Cl electrolytic complexes, the complexes [Au (L)3]Cl3 and [Ni (L)2]Cl2  were suggested to have square planar geometry. The resulting products were characterized using 1H-NMR, UV-Vis, IR spectroscopy, conductivity and EDX.